Pelayanan Bimbingan dan Konseling Guru Kelas Terhadap Siswa di Sekolah Dasar Islam Terpadu - nurlaili -; Nurhayati -; Mega Iswari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Recently, the guidance and counseling program has become increasingly important to all educational institutions, particularly primary schools, to help students cope with daily challenges which have had disastrous consequences for their personal lives, school structures, and society. This study aims to determine how classroom teachers implemented guidance and one of counseling services for students at Cahaya Hati Integrated Islamic Elementary School, Bukittinggi. To accomplish this goal, the author distributed questionnaires to twelve class teachers and conducted interviews with two class teachers and one counseling guidance teachers at the Cahaya Hati Integrated Islamic School, Bukittinggi. This study focused on the implementation of guidance and counseling services, as well as supporting activities carried out by classroom teachers. According to the study’s findings, classroom teachers provided counseling services to students such as orientation services, information services, placement services, learning service, consulting services, and mediation services. This is demonstrated by the percentage of questionnaire responses indicating that there are no teachers who have never performed this service. Furthermore, based on results, it was discovered that several classroom teachers had never carried out supporting activities such as home visits and meeting with authorities in dealing with serious problems. The study’s findings also show that there is good cooperation among school personnel in dealing with student problems and needs.